Discrepancies between clinical and pathologic staging in tumors of the larynx: Evaluation of the probable causes and influence in overall survival - Fontes Lima, António (2021)
Introduction: TNM staging plays a central role in therapeutic decision-making, being also useful for estimating prognosis. Clinical staging (cTNM) is based on physical examination, endoscopy e imaging studies. Pathological staging (pTNM) is based on histopathological analysis after the surgical procedure. Discrepancies between cTNM and pTNM in larynx cancer have been reported in the literature, but some controversies remain.  Material and methods: a retrospective analysis of the patients who underwent surgery for larynx cancer (LC) in Hospital de Braga between January of 2013 and December of 2017 was performed. Patients who underwent total laryngectomy (TL) and partial laryngectomy (PL) associated with neck dissection. The following data were retrieved: age, gender, location, cTNM, and pTNM, time between first histopathological diagnosis and surgery, 5-year overall survival (OS), relapse, and death. For analysis purposes, the staging was performed according to American Joint Committee on Cancer 8th Edition, 2017.  Results: of the 72 patients diagnosed with LC, 47 were included in the analysis. 17% (n=8) underwent PL, while 83% (n=39) underwent TL. There was a discrepancy between cTNM and pTNM in 66% of the patients: a different T in 44,7%, with a low Cohen Kappa coefficient of 0,310 (p = 0,01), and a different N in 29,8%, with a substantial Cohen Kappa coefficient of 0,688 (p < 0,001). The most common reason for upstaging T was the invasion of the outer cortex of the thyroid cartilage, and the most frequent reason for downstaging was apparent vocal cord fixation in the preoperative examination. The median of the days between histopathological diagnosis and surgery in the patients whose T was upstaged was significantly different (superior) than other patients. Tumors located in the glottis were associated with a T downstaging (p = 0,020). There was no statistically significant difference in survival curves between patients with and without discrepancies in cTNM and pTNM.  Discussion and conclusions: our results show higher rates of re-staging than the ones described in the literature, that vary between 20 and 55%. New evaluation methods, such as imaging studies with better diagnostic accuracy, and, on the other hand, reducing the time between first diagnosis and surgical treatment may be important to reduce the rates of discrepancy between cTNM and pTNM. Despite re-staging being frequent, according to our data, it is not associated with worse OS.